ICESat‐derived inland water surface spot heights. Issue 4 (1st April 2016) - O'Loughlin, Fiachra E.; Neal, Jeffrey; Yamazaki, Dai; Bates, Paul D.
Abstract: Accurate measurement of water surface height is key to many fields in hydrology and limnology. Satellite radar and laser altimetry have been shown to be useful means of obtaining such data where no ground gauging stations exist, and the accuracy of different satellite instruments is now reasonably well understood. Past validation studies have shown water surface height data from the ICESat instrument to have the highest vertical accuracy (mean absolute errors of ∼10 cm for ICESat, compared, for example, with ∼28 cm from Envisat), yet no freely available source of processed ICESat data currently exists for inland water bodies. Here we present a database of processed and quality checked ICESat‐derived inland water surface heights (IWSH) for water bodies greater than 3 arc sec (∼92 m at the equator) in width. Four automated methods for removing spurious observations or outliers were investigated, along with the impact of using different water masks. We find that the best performing method ensures that observations used are completely surrounded by water in the SRTM Water Body data. Using this method for removing spurious observations, we estimate transect‐averaged water surface heights at 587, 292 unique locations from 2003 to 2009, with the number of locations proportional to the size of the river. Key Points: We present a database of ICESat water surface heights for water bodies wider than 3 arc sec Four outlier removal methods were investigated, along with the impact of using different water masks We estimate transect‐averaged water surface heights at 587, 292 unique locations and times globally